Studi mengenai Hambatan Menyusui pada Ibu Bayi Usia 0-2 Tahun - Kartini, Monica; Purnamiasih, Desak Putu Kristian (Jurnal Kesehatan, 2024)
WHO recommends exclusive breastfeeding because of its short-term and long-term benefits for infants and mothers. However, the coverage of exclusive breastfeeding has not yet reached the expected target. This study aims to describe breastfeeding barriers experienced or felt by breastfeeding mothers and to determine the relationship between breastfeeding barriers and maternal demographic variables. The study was conducted using quantitative methods and a cross-sectional approach. The study subjects were mothers with infants aged 0-2 years in the Bulu Health Center work area, Temanggung Regency, a total of 122 people were taken using the cluster-random sampling technique. The data obtained were analyzed using descriptive statistics and Spearman correlation analysis. The results showed that the most common breastfeeding barriers felt by respondents were experiencing sore nipples (59%), being embarrassed to breastfeed in public (54.1%), swollen breasts (51.2%), feeling inadequate knowledge about breastfeeding (40.5%), and feeling pain after childbirth (38.5%). Correlational analysis showed no significant relationship between breastfeeding barriers and maternal age, number of children, maternal education, occupation, and type of delivery (p-value>0.05). In conclusion, most mothers experience at least one barrier to breastfeeding. Appropriate interventions are needed to address these barriers, especially in terms of increasing the knowledge of mothers or prospective mothers about lactation so that they can prevent breast problems. Further qualitative research is needed to explore the barriers or supporting factors in providing exclusive breastfeeding.